2009
DOI: 10.1038/gt.2009.158
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory efficacy of hypoxia-inducible factor 1α short hairpin RNA plasmid DNA-loaded poly (D, L-lactide-co-glycolide) nanoparticles on choroidal neovascularization in a laser-induced rat model

Abstract: The aim of this study was to evaluate the possibility of poly (D, L-lactide-co-glycolide) nanoparticle (NPs) as a gene vector for functional plasmid DNA (pDNA) and to investigate its inhibitory efficacy on experimental choroidal neovascularization (CNV). We developed intravitreal administered, hypoxia-inducible factor 1a (HIF-1a) short hairpin RNA and green fluorescent protein (GFP) co-expressed pDNA-loaded NPs (pshHIF-1a NPs). CNV was induced by laser photocoagulation in 112 rats. The rats were then randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 71 publications
3
31
1
Order By: Relevance
“…Laser-induced choroidal neovascularization (CNV) is an established model of pathologic ocular angiogenesis (16). Hif-1α and VEGF protein expression are significantly increased in CNV lesions, and it is conceivable that Nutlin-3-mediated antiangiogenesis also occurs through Hif-1α (17). We performed a single intravitreal injection of racemic Nutlin-3 or DMSO immediately after laser injury and demonstrated that, after 7 days, Nutlin-3 inhibits pathologic retinal angiogenesis in a dosedependent fashion, with peak effect at 10 ng/μl (17.2 μM) (Figure 8, A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Laser-induced choroidal neovascularization (CNV) is an established model of pathologic ocular angiogenesis (16). Hif-1α and VEGF protein expression are significantly increased in CNV lesions, and it is conceivable that Nutlin-3-mediated antiangiogenesis also occurs through Hif-1α (17). We performed a single intravitreal injection of racemic Nutlin-3 or DMSO immediately after laser injury and demonstrated that, after 7 days, Nutlin-3 inhibits pathologic retinal angiogenesis in a dosedependent fashion, with peak effect at 10 ng/μl (17.2 μM) (Figure 8, A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Increased levels of HIF-1 have also been found in CNV lesions from both AMD patients and laser-induced CNV (Vinores et al 2006 ;Zhang et al 2007 ;Sheridan et al 2009 ) . Zhang et al have shown that inhibition of HIF-1 by shRNA can effectively reduce VEGF-induced neovascularization in the laser model (Zhang et al 2010 ) . Also, Vinores et al described that removal of the HRE (the binding site for HIF-1) from the VEGF promoter resulted in a tenfold reduction in the size of laser-induced CNV lesions in mice (Vinores et al 2006 ) .…”
Section: Hypoxia-regulated Expressionmentioning
confidence: 99%
“…A mature platform in development of different versions of silencing is viroid that target specific cell lines. Adeno-associated viruses, adenoviruses (e.g., Ad5), retroviruses (e.g., MoMLV and lentiviruses) and herpes simplex virus are among widely used viral vectors [98,99]. Lentiviral and adenoviral let7 antagomiRs (also known as blockmirs or anti-miRs) has been used to target NSCLC through intranasal delivery methods in murine [73,100].…”
Section: Viral Carriersmentioning
confidence: 99%